2011
DOI: 10.15193/zntj/2011/77/036-044
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Black Elder Flowers and Berries Harvested From the Wild

Abstract:  WŁAŚCIOWŚCI PRZECIWUTLENIAJĄCE KWIATÓW I OWOCÓW BZU CZARNEGO POZYSKIWANEGO ZE STANU NATURALNEGOS t r e s z c z e n i e W pracy przedstawiono wyniki badań dotyczących właściwości przeciwutleniających ekstraktów wodnych z kwiatów oraz owoców bzu czarnego zbieranego z 17 miejsc naturalnego występowania w Polsce oraz oceniono wpływ zawartości polifenoli ogółem na właściwości przeciwutleniające badanych surowców. Stwierdzono, że kwiaty bzu czarnego zawierały więcej związków polifenolowych niż owoce pochodzące z t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
5
1
Order By: Relevance
“…The elderberry fruit, analyzed in this study, had an equal or higher antioxidant capacity as compared with flowers of the same cultivars or wild plants from the same locations (Figure 1.). This stands in contrast to earlier studies by Dawidowicz et al (2006) [20] and Kołodziej et al (2011) [21] who used the DPPH (2,2-diphenyl-1-picrylhydrazyl) and FRAP (Ferric Reducing Antioxidant Power) methods for their measurements and found higher radical scavenging activity in elderberry flowers. In addition, fruit and flowers of the analyzed cultivars demonstrated significantly higher antioxidant activity that those harvested from wild growing plants (Table 3).…”
Section: Antioxidant Capacity (Ac) Of Elderberry Flower and Fruit Extcontrasting
confidence: 93%
See 1 more Smart Citation
“…The elderberry fruit, analyzed in this study, had an equal or higher antioxidant capacity as compared with flowers of the same cultivars or wild plants from the same locations (Figure 1.). This stands in contrast to earlier studies by Dawidowicz et al (2006) [20] and Kołodziej et al (2011) [21] who used the DPPH (2,2-diphenyl-1-picrylhydrazyl) and FRAP (Ferric Reducing Antioxidant Power) methods for their measurements and found higher radical scavenging activity in elderberry flowers. In addition, fruit and flowers of the analyzed cultivars demonstrated significantly higher antioxidant activity that those harvested from wild growing plants (Table 3).…”
Section: Antioxidant Capacity (Ac) Of Elderberry Flower and Fruit Extcontrasting
confidence: 93%
“…The correlation coefficient was 0.93 for fruit and 0.97 for flowers (Table 4). Kołodziej et al (2011) showed that elderberry flowers contained more phenolic compounds than elderberry fruit collected from the same locations. A similar observation was made for infusions from dried elderberry flowers and dried elderberry fruit; flowers were always found to be richer in various phenolic compounds, especially flavonoids, than in the fruit [21,27].…”
Section: Total Phenolic Content (Tpc) Of Elderberry Flower and Fruit mentioning
confidence: 98%
“…The researchers showed the amount found in flowers ranged from 78.96 to 110.51 mg 100 −1 FW (fresh weight), compared with as little as between 3.39 and 9.84 mg 100 −1 FW in fruit. A similar association was demonstrated by Kołodziej and Drożdżal [24], who analyzed the flowers and fruit of elderberry. Elderflowers had a higher content of polyphenolic compounds (from 37.02 to 53.33 mg g −1 DM [dry mass]) compared with elderberries (from 26.84 to 44.8 mg g −1 DM) as well as greater antioxidant capacity than the fruit, which was confirmed using FRAP and DPPH assays.…”
Section: Antioxidant Potentialsupporting
confidence: 79%
“…Its fl owers and ripe fruits are used as raw herb material (Kołodziej and Drożdżal, 2011). Due to its content of a poisonous glycoside, sambunigrin, its fruits may be consumed only after thermal processing.…”
mentioning
confidence: 99%